THE INFLUENCE OF TEACHER COMPETENCY ON STUDENT TALENT INTEREST WITH TEACHER PERFORMANCE AS A MEDIATING VARIABLE - Rance Rahmadika; Muhammad Jaya (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2025)
This study aims to examine the influence of teacher competence on student learning achievement with teacher performance as a mediating variable. A quantitative approach was employed using Structural Equation Modeling (SEM) with a sample of 183 high school teachers in Padang City. Based on the results of the study, it was obtained that competence had a positive and significant effect on the performance of high school teachers in Padang City, while competency assessment of student learning achievement had positive and insignificant results on high school student learning achievement in Padang City. The results of the intervening variable test obtained that competency assessment had a positive and significant effect on high school student learning achievement in Padang City through teacher performance, direct competency assessment of student learning achievement if teacher performance had a significant effect on student learning achievement. This study contributes by clarifying the mediating role of teacher performance and providing practical insights for improving educational quality.